Gender, sexual orientation, ethnicity and socioeconomic factors influence how wildland firefighters communicate their work experiences - Ragland, Miranda; Harrell, Jennifer; Ripper, Molly; Pearson, Seth; Granberg, Rachel; Verble, Robin (Frontiers in Communication, 2023)
As climates change, natural resource professionals are often working on the frontlines of intensifying environmental disasters, acting in both scientific and emergency response roles. One subset of this group, wildland firefighters often engage in multifaceted careers that incorporate elements of resource planning, conservation management, community disaster relief, and operational management. Despite these STEM roles and nearly half (48%) of them having earned at least a bachelor’s degree, usually in a STEM field, wildland firefighters are almost exclusively lumped with emergency responders in the scientific literature. We surveyed 708 wildland firefighters with 9 open response questions as part of a larger survey asking about experiences and attitudes in the United States federal workplace. From their responses and voluntarily provided demographic data, we extracted information about response length, use of hedges, tag questions and imperatives, use of personal language, use of expletives and derogatory language, use of apologetic language, and the types of responses provided. We then analyzed whether certain demographic and socioeconomic factors were statistical predictors of language use in wildland firefighter survey responses with the goal of ultimately providing a framework for differentiating and identifying factors that may influence employee retention, attitudes, morale, and experiences among wildland firefighter sub-demographics. We found that different demographic groups varied in their responses to questions: Minority groups used fewer words and were more likely to relate personal experiences than majority groups.